Improving Citizen’s Life Skill Learning by Tenun Training - Simbolon, Gallex; Elnovreny, Jane (Universitas Negeri Padang, 2020)
The decrease of agricultural and plantation land in the East Penfui area because of many lands have been converted into residential areas, It makes most people who work as farmers reduce their income and even cause unemployment. This research was made to overcome this issue,as alternative to local society to obtain and developing human resources by training them in life skill especially in tenun training. The training process shows the occurrence of the learning process to participants so that they can improve their abilities and performance individually to overcome their problems that are being faced. Tenun ikat are expected can be able to maintain the cultural heritage of their ancestors and good prospects for increasing income. This research was conducted at Rindu Sejahtera PKBM, Kupang in 2018. The research type of this study is qualitative research with a case study method. The subject or informant in this study determined by a purposive technique, that is, the researcher has a tendency to choose informants who are considered to know information and problems deeply and can be trusted to be a valid source of data. The subjects of this research process consisted of 5 peoples; they are one manager and four trainees. The result of this research shows : (1) the results of the training program were successfully obtained by residents learning most of the skills about weaving, most residents learned after participating in activities involving small groups and men who then independently marketed them, so they could increase funding and increase learning time, (2) the supporting factors in organizing this training are supporters in the village in the form of funds from village managers who are able to bring in facilitators who are experts in the field of weaving and the availability of appropriate facilities and infrastructure, interest in research high learning also helps support the course of training, (3)the strategic location of the training site, PKBM Rindu Sejahtera is in the middle of residential areas so it is easy for the trainees to go to during the training. The results also showed that there were several factors which became obstacles during the implementation of the training activities including, (1) relatively short training time, the training participants hoped that the implementation time could be longer so that they could know more about weaving both making patterns, modifying until the final process weaving, (2) limited tutors, tutors invited to provide guidance to the training participants are only one person, so sometimes it is difficult to divide time especially when practice is done.